Global epidemiology and socioeconomic correlates of hypopharyngeal cancer in 2020 and its projection to 2040: findings from GLOBOCAN 2020 - Mousavi, Seyed Ehsan; Ilaghi, Mehran; Mirzazadeh, Yasaman; Mosavi Jarrahi, Alireza; Nejadghaderi, Seyed Aria (Frontiers in Oncology, 2024)
Background: Hypopharyngeal cancer (HC) comprises less than 5% of all malignant tumors in the head and neck. They often present at an advanced stage, thereby resulting in high mortalities. We aimed to report the epidemiology of HC globally, regionally, and nationally by age, sex, and socioeconomic status in 2020 and its projection to 2040. Methods: Data on HC incidence and mortality were extracted from the GLOBOCAN 2020. Age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR), and mortality-to-incidence ratios (MIRs) were calculated. We used bivariate correlation test, presenting results through Pearson's correlation coefficient (r) to investigate the correlation between the metrics, human development index (HDI), and current healthcare expenditure (CHE) as a percentage of gross domestic product (GDP) (CHE/GDP). Results: In 2020, there were 84254 new HC cases globally (ASIR: 0.91 per 100000). Moreover, HC resulted in 38599 mortalities in 2020 (ASMR: 0.41). Furthermore, the global MIR of HC was 0.45. The ASIR and ASMR of HC were higher in men than women. Also, HDI demonstrated weak significant correlations with HC ASIR (r= 0.249, p<0.01), ASMR (r= 0.185, p<0.05), and MIR (r= 0.347, p<0.001). Moreover, a weak significant correlation was also observed between CHE/GDP and MIR (r= 0.279, p<0.001). The number of new HC cases and mortalities were estimated to increase by 50% and 55% in 2040, respectively. Conclusion: HC is a relatively rare cancer but with a substantial gender and geographic divide in distribution. Key priorities should thus include establishing high-quality cancer registries worldwide.